Anterior synechiae after penetrating keratoplasty in infants and children with Peters’ anomaly - Yujing Yang; Jun Xiang; Jianjiang Xu (BMC Ophthalmology, 2022)
Abstract Background To evaluate anterior synechiae after penetrating keratoplasty (PK) in patients with Peters’ anomaly using anterior segment optical coherence tomography (OCT). Methods A retrospective cross-sectional study was performed. The medical records of patients diagnosed with Peters’ anomaly who underwent PK between 2013 and 2018 were reviewed. In addition to basic ophthalmic examinations, images of anterior segment structures were obtained via spectral-domain OCT at baseline and during the postoperative follow-up period. The profiles of postoperative anterior synechiae and multiple potential risk factors were analyzed. Results Seventy-one eyes of 58 patients, aged 5 to 23 months, were included. Various extent of postoperative anterior synechiae was observed in 59 eyes (83.1%). OCT findings revealed graft-host junction synechiae, peripheral anterior synechiae, and a combination of both. Disease severity and malposition of the internal graft-host junction were significantly associated with the formation of postoperative synechiae. Multivariate regression analysis found that preexisting iridocorneal adhesion [odds ratio (OR) = 16.639, 95% confidence interval (CI) 1.494–185.294, p = 0.022] was positively correlated with postoperative anterior synechiae, whereas anterior chamber depth (OR = 0.009, 95% CI 0.000–0.360, p = 0.012) and graft size (OR = 0.016, 95% CI 0.000–0.529, p = 0.020) were negatively correlated with postoperative synechiae. In addition, quadrants of preexisting iridocorneal adhesion and width of the host corneal bed were identified as risk factors for increased postoperative anterior synechiae. Conclusions Anterior synechiae following PK is a relatively common occurrence in Peters’ anomaly patients and is found to be associated with preexisting iridocorneal adhesion, a shallow anterior chamber, small graft size, graft-host junction malposition, and graft closer to the corneal limbus. These data indicate the need for careful consideration when performing PK on these patients.